Understanding astrocyte-derived extracellular vesicles in health and disease - White, Katherine (2024)
Astrocytes are glial cells within the brain responsible for maintaining healthy brain function. They also have the ability to react to harmful stimuli by changing into a reactive phenotype in order to protect the brain alongside microglia. Extracellular vesicles (EVs) are released from all cell types within the central nervous system (CNS) and are thought to represent the phenotype of the cell at the time of release. Therefore astrocyte-derived EVs (ADEVs) were hypothesised to change to represent the reactive state of the astrocytes, making them useful tools to monitor brain health. The aim of this thesis was to better understand ADEVs from both quiescent and reactive astrocytes, as well as how they may change in disease.